2011
DOI: 10.1016/s0016-5085(11)62456-6
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Bacteriotherapy for Ulcerative Colitis; Patients Are Ready, Are We?

Abstract: Background-Fecal bacteriotherapy (FB) has been proposed as a safe and effective alternative treatment for a number of gastrointestinal conditions including ulcerative colitis (UC). We performed a qualitative study to explore the attitudes and concerns of adult patients and parents of children with UC regarding FB as a potential treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…How FMT should be regulated remains contentious—particularly whether the feces should be considered a therapeutic “drug,” a biologic product or tissue . Patients have stated that they would be willing to receive FMT for recurrent CDI if it is recommended by their treating physician . Given this willingness and the other benefits of FMT compared with antibiotic therapy, the inclusion of FMT as standard care for recurrent CDI is justified.…”
Section: Discussionmentioning
confidence: 99%
“…How FMT should be regulated remains contentious—particularly whether the feces should be considered a therapeutic “drug,” a biologic product or tissue . Patients have stated that they would be willing to receive FMT for recurrent CDI if it is recommended by their treating physician . Given this willingness and the other benefits of FMT compared with antibiotic therapy, the inclusion of FMT as standard care for recurrent CDI is justified.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies suggested that patients would actually be very interested in performing FMT in a hospital setting as a treatment for their IBD [37,38]. Here, we aimed to assess the view of a broad number of IBD patients with respect to FMT as a potential treatment option.…”
Section: Introductionmentioning
confidence: 99%
“…In a survey of 73 physicians, 25 (34%) indicated they would be unwilling to perform the procedure with the most common concerns being patient acceptance and tolerability (71%) followed by safety (60%) and efficacy (57%) . In contrast, in a recent qualitative study exploring readiness for FMT in patients with UC, the majority of patients wished the procedure was already available and most viewed it as being safer than current available therapies, especially steroids or biological therapies . In a quantitative extension of this study, the majority of UC patients were interested or willing to consider FMT despite reporting disease control with IBD medications .…”
Section: Discussionmentioning
confidence: 86%